Continuous dependence of the solution of a parabolic equation in a Hilbert space on the parameters and initial data - Otelbaev, M.; Zhapsarbaeva, L. K. (Differential equations, 2009)
We present classes of equations for which weak a priori estimates hold and prove the global strong solvability of one system of equations.